Digital Innovation in Public Services: A Case Study of Digital Platform Implementation in South Sulawesi - Hernawan, Hernawan (PINISI Discretion Review, 2024)
Digital innovation has become a key driver in transforming public services, enhancing efficiency, transparency, and accessibility. Governments worldwide, including Indonesia, have increasingly adopted digital platforms to streamline administrative processes and improve service delivery. This study examines the implementation of digital platforms in South Sulawesi’s public services, identifying their benefits and challenges while exploring solutions for sustainable digital governance. A qualitative case study approach was employed, utilizing semi-structured interviews with key stakeholders, document analysis, and field observations. Participants included government officials, IT developers, and end-users such as citizens and service providers. The study analyzed various digital platforms used for administrative services, tax payments, and public complaints management, highlighting both successes and limitations. The findings indicate that digital platforms have significantly improved administrative efficiency and citizen engagement by reducing bureaucratic bottlenecks and increasing service transparency. However, challenges persist, particularly the digital divide, where limited infrastructure and digital literacy hinder adoption, especially in rural areas. System integration issues were also observed, as some platforms lack interoperability with government databases, leading to inefficiencies. Additionally, cybersecurity concerns remain a major risk, with inadequate data protection exposing sensitive citizen information. To ensure the sustainability of digital governance, this study highlights the importance of capacity-building programs, infrastructure development, and regulatory frameworks. Strengthening public-private partnerships and integrating citizen feedback mechanisms are also critical for optimizing digital service delivery. Ultimately, a strategic, inclusive, and well-integrated approach is necessary to maximize digital platform benefits and drive long-term improvements in public service governance.